2008
DOI: 10.1111/j.1399-5618.2007.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar II disorder: arguments for and against a distinct diagnostic entity

Abstract: Bipolar II disorder is supported as a distinct category within mood disorders, but the definition and boundaries deserve a greater clarification in the DSM-V and ICD-11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(121 citation statements)
references
References 147 publications
(160 reference statements)
8
110
2
1
Order By: Relevance
“…For some patients, hypomania causes no to minimal functional impairment and may even be associated with brief periods of above‐normal functioning. However, prolonged, relatively severe, or mixed or irritable hypomania may be impairing 423. Treatment should include discontinuing agents that can worsen or prolong symptoms, including antidepressants and stimulants, and initiating appropriate pharmacotherapy.…”
Section: Bipolar II Disordermentioning
confidence: 99%
“…For some patients, hypomania causes no to minimal functional impairment and may even be associated with brief periods of above‐normal functioning. However, prolonged, relatively severe, or mixed or irritable hypomania may be impairing 423. Treatment should include discontinuing agents that can worsen or prolong symptoms, including antidepressants and stimulants, and initiating appropriate pharmacotherapy.…”
Section: Bipolar II Disordermentioning
confidence: 99%
“…Findings on neurocognitive differences between the two subtypes can be used as markers in research for underlying neurobiological distinguishers using neuroimaging techniques. Neuroimaging and genetics might be useful in validating BD II diagnostic subtype (Vieta & Suppes, 2008). Some genetic studies have suggested that BD II and BD I ' breed true ' in families ; therefore, in further studies it would be interesting to correlate clinical and neuropsychological data with genetic data in BD II patients.…”
Section: Future Directionsmentioning
confidence: 99%
“…Many clinicians still consider BD II as a mild form of classical BD, although the data indicate that it may be associated with high morbidity and mortality, including higher episode frequency, co-morbidity, suicidal behaviour and rapid cycling as compared with BD I (Vieta et al 1997(Vieta et al , 1999. Misdiagnosing BD II may also affect therapeutic decisions and therefore the course and prognosis of bipolar patients (Vieta & Suppes, 2008). An early age at onset of BD II has been associated with a higher degree of severity, a poorer treatment response and a worse prognosis (Engstrom et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When Bipolar II was introduced into the DSM in 1994, some argued that it should be considered a variant of Major Depression (Kupfer, Carpenter, & Frank, 1988). Recent data identifying genes associated with Bipolar I and Bipolar II suggest that common genes are not identified according to Vieta & Suppes (2008). Judd et al (2003) concur that current genetic evidence suggests that Bipolar I and Bipolar II do not share a Evidenced-based 7 common genetic diathesis.…”
Section: How the Change In Diagnostics Created An Epidemicmentioning
confidence: 99%